Trauma-Informed Yoga: Investigating an Intervention for Mitigating Adverse Childhood Experiences in Rural Contexts. Issue 4 (4th July 2022) - Davis, Lauren; Aylward, Alexandra; Buchanan, Rebecca
Abstract: In a state ravaged by suicide and a mental health crisis, this study sought to mitigate impacts of adverse childhood experiences (ACEs) and depressive and anxiety symptomology in high school students in a rural Montana community. Through a seven-week, twice weekly intervention of trauma-informed yoga, participants experienced statistically significant reductions in anxiety (GAD-7) and increases in Strengths and Difficulties (SDQ-11) overall scores and some subscales; noteworthy improvements were also present in depressive symptomatology (PHQ-A), salivary cortisol levels, and sleep duration. Importantly, participant qualitative feedback indicated significant benefits in focus, relaxation, and overall well-being. Further research is needed to imply generalizability and should include a larger, more diverse sample as well as utilization of control groups and an examination of academic and behavioral impacts at the school level.